Successful ablation of lymph nodes using irreversible electroporation (IRE) in a porcine survival model - Fritz, Stefan; Sommer, Christof-Matthias; Radeleff, Boris; Werner, Jens; Hackert, Thilo (Langenbeck's archives of surgery, 2017)
BackgroundIrreversible electroporation (IRE), a nonthermal injury ablation technique, has been shown to be effective and safe in various organs, such as in the kidney, liver, prostate, or in pancreas. In contrast to radiofrequency or microwave ablation, IRE is also effective in the neighborhood of major vessels. Many human cancers reveal lymphatic spread. The present study aimed to evaluate technical feasibility and safety of IRE in lymphatic tissue. To our knowledge, this is the first report showing successful IRE of lymph nodes in a standardized porcine survival model.MethodsA total of ten pigs were divided into two study groups. Five animals received ECG-gated IRE of mesenteric lymph nodes of the small bowel and were sacrificed 2 h after ablation. Another five animals were followed up for 7 days. Clinical parameters, laboratory and abdominal imaging by contrast-enhanced computed tomography, as well as histology were obtained from all animals at different time points.ResultsDuring and after IRE ablation, no cardiocirculatory side effects were noted in any of the animals. In the acute phase experiments, no damage to adjacent organs and no thermal injuries were seen following IRE. One hundred twenty minutes after ablation, no significant laboratory changes were observed. In the survival group, all animals recovered quickly and showed normal activity and feeding habits indicating a minimal pain level. Seven days after IRE ablation, a significant increase in white blood cell count was observed, while creatinine, urea, or hemoglobin remained unchanged. Computed tomography revealed a hypodense lesion following IRE already at 2 h. Histopathology showed coagulation necrosis of the treated lymph nodes with preservation of the lymph node capsule.ConclusionsThis porcine survival model shows that IRE can safely and effectively be performed in lymph nodes. Thus, IRE might display a novel approach for therapy of lymph node metastasis. Further clinical studies are needed to evaluate the oncologic outcome of IRE ablation in lymph node metastasis.